Pleomorphic hyalinizing angiectatic tumor arising in the groin: A case report - Onyemkpa, Chibueze (Int J Surg Case Rep, 2016)
INTRODUCTION: Pleomorphic hyalinizing angiectatic tumors are a rare group of tumors that are currently classified as benign tumors of unknown differentiation. To our knowledge, less than 100 cases have been reported in literature. We report a case that presented in the groin – an uncommon location for this rare tumor. CASE REPORT: A 75 year-old female presented with a seven-year history of painless right groin mass with rapid growth of 2 year duration. On physical examination, a firm and mobile mass was identified in the right groin. It measured 12 cm × 8 cm, with no clinically palpable lymph nodes. Microscopic and immunohistochemical features were consistent with pleomorphic hyalinizing angiectatic tumor. DISCUSSION: Pleomorphic hyalinizing angiectatic tumor is a rare soft tissue tumor usually diagnosed using microscopic and immuohistochemical analysis to allow for differentiation from other soft tissue tumors. It is treated by wide local excision.